Bilateral renal leiomyoma with 5 year follow-up: Case report - Goren, Mehmet Resit; Erbay, Gurcan; Ozer, Cevahir; Goren, Vinil; Bal, Nebil (Canadian Urological Association Journal, 2015)
Renal leiomyomas are exceptionally rare benign tumours of the kidney. Although the renal leiomyomas usually do not metastasize, the differential diagnosis between renal leiomyomas and malign lesions (leiomyosarcoma or renal cell carcinoma) cannot be done by radiological examinations, but is possible by histological examination. Surgery is the preferred treatment. After surgery, the prognosis is excellent without recurrence. Although uterine leiomyomas can be multicentric, renal leiomyomas have been single lesions. We report an incidentally detected case of bilateral renal leiomyoma in a 50-year-old woman with a 5-year follow-up. We also review the literature and discuss clinical, radiological and histological features of renal leiomyomas.